Spoken discourse markers and English language teaching: practices and pedagogies - Jones, Christian (2011)
This thesis reports on a mixed methods classroom research study carried out at a British university. The study investigates the effectiveness of two different explicit teaching approaches, Illustration – Interaction – Induction (III) and Present – Practice – Produce (PPP) used to teach the same spoken discourse markers to two different groups of Chinese learners at the same level of language competency. It was hypothesised that one explicit teaching approach would be more effective than the other in terms of both short and longer term acquisition and both would be more effective than no teaching when viewed objectively with test data and subjectively by the learners themselves.